0
$\begingroup$

Notation: let us have a particle of spin(more generally angular momentum, but for simplicity just consider spin) $j_1$ with projection to the third axis $m_1$ and a particle with spin $j_2$ with projection of $m_2$. We want to combine them into a doublet with total spin $J$ and its projection $M$. We write clebsch-gordan coefficient $( j_1 m_1 j_2 m_2 | J M )$.

Now consider we have two clebsh-gordan coefficients that we want to multiply: $$\sum_{M\in\{-J,..,J\}}( j_1 m_1 j_2 m_2 | J M )(j'_1 m'_1 j'_2 m'_2 | J M )$$ my question is: Is there a simple formula this can be reduced into?

$\endgroup$
1
$\begingroup$

Quoting Wikipedia on Clebsch-Gordan coefficients we have the orthogonality relation:

$$\sum^{j_1+j_2}_{J=|j_1-j_2|}\sum^{J}_{M=-J}<j_1,m_1,j_2,m_2|J,M><J,M|j_1,m'_1,j_2,m'_2>=\\=<j_1,m_1,j_2,m_2|j_1,m'_1,j_2,m'_2>=\delta_{m_1,m'_1}\delta_{m_2,m'_2}$$

This is the closest I could find resembling what you presented above. I hope this helps.

$\endgroup$
  • $\begingroup$ Yeah, thanks, that really helped. I actually had to compute a special case when J=2 and $j_1=j_2=j'_1=j'_2=1$ and sum over the rest of $m$(in other words a product of two spherical tensors made of vector operators), so I know, that $( 1 1 1 -1 | 1 0 )=-( 1 -1 1 1 | 1 0 )$ and simmilarly for J=M=1, this will sum to zero and I am left with only the case of J=M=0, which is much easier to compute than 5 cases of M for J=2 $\endgroup$ – user74200 May 25 '18 at 0:00
0
$\begingroup$

The simplest way to look at such sums is to start with $$ \langle j_1m_1; j_2m_2\vert j_1’m_1’; j_2’m_2’\rangle = \delta_{j_1j_1’}\delta_{j_2j_2’}\delta_{m_1m_1’}\delta_{m_2m_2’}\, , $$ insert the unit operator in the form of $$ 1= \sum_{JM}\vert JM\rangle\langle JM\vert $$ where $J$ runs over all the allowed value in the coupling $j_1\otimes j_2$, $M$ runs from $-J$ to $J$, so as to get $$ \sum_{JM}\langle j_1m_1; j_2m_2\vert JM\rangle \langle JM\vert j_1’m_1’; j_2’m_2’\rangle = \delta_{j_1j_1’}\delta_{j_2j_2’}\delta_{m_1m_1’}\delta_{m_2m_2’} \tag{1} $$ and recall that the CGs are real, i.e. $$ \langle JM\vert j_1’m_1’;j_2’m_2’\rangle = \langle j_1’m_1’;j_2’m_2’\vert JM\rangle \tag{2}\, . $$ Inserting (2) in (1) gives the desired orthogonality relation.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.